2018
DOI: 10.1111/jog.13635
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 246 sentinel lymph node biopsies of patients with clinical primary breast cancer by application of carbon nanoparticle suspension

Abstract: Sentinel lymph node biopsy performed using the nanocarbon staining method is simple, easy and reliable, and it can be used to predict the axillary status of breast cancer in the early stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In recent years, CNS has proven to be beneficial as a lymph node tracer that allows lymph nodes to be explored during surgery for breast cancer, thyroid cancer and gastric cancer 15,22,23 . For cervical cancer, the application of CNS was attempted with SLNB in a limited sample size of 40 patients in 2017, with DR of 95% (38/40), sensitivity of 100% (5/5) and NPV of 100% 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, CNS has proven to be beneficial as a lymph node tracer that allows lymph nodes to be explored during surgery for breast cancer, thyroid cancer and gastric cancer 15,22,23 . For cervical cancer, the application of CNS was attempted with SLNB in a limited sample size of 40 patients in 2017, with DR of 95% (38/40), sensitivity of 100% (5/5) and NPV of 100% 12 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous cervical cancer study showed that performing SLNB with CNS resulted in easy identification, with good lymphatic tracer effects, and results in increased lymph node retrieval 12 . CNS has been applied in early breast cancer and mid‐low rectal cancer, and has detection and predictive values for SLNBs 13‐15 . Its use in SLNB for cervical cancer is relatively new.…”
Section: Introductionmentioning
confidence: 99%
“…In China, CNSs have been widely used for the intraoperative identification of SLNs in various cancers, and have been found to have high detection rates and accuracy (45)(46)(47). CNSs can be used successfully for SLN identification in patients with early BC (39), and have been shown to have a higher SLNB success rate than nanocarbon staining (99.59%, with 97.06% accuracy and 93.22% sensitivity), and a lower false-negative rate (6.78%) (48). The detection rate of the CNS-alone method was lower than that of the ICG + MB method (98.3% vs. 100%); however, the difference was not significant (49).…”
Section: Discussionmentioning
confidence: 99%
“…After macrophage phagocytosis, the particles accumulate in the lymph nodes and dye them black . This unique selective accumulation of carbon nanoparticles is being used to make lymph node retrieval more efficient in certain types of surgery . The accompanying video (Video in the online Supporting Information) demonstrates the feasibility of using ACNS as a tracer to facilitate radical ALN dissection in laparoscopic rectal cancer surgery.…”
mentioning
confidence: 99%